Nanoporous graphene by quantum dots removal from graphene and its conversion to a potential oxygen reduction electrocatalyst via nitrogen doping - Palaniselvam, Thangavelu; Valappil, Manila Ozhukil; Illathvalappil, Rajith; Kurungot, Sreekumar (Energy & Environmental Science, 2014)
A simple way to produce an efficient metal-free oxygen reduction electrocatalyst from graphene by generating nanopores in the matrix and subsequently establishing nitrogen-doped active sites along the pore openings is demonstrated. Well-structured nanoporous graphene (pGr) and photoluminescent graphene quantum dots (GQDs) could be simultaneously generated by a chemically assisted oxidative treatment of graphene. The process helped to knock out small pieces of Gr through epoxide formation, which subsequently resulted in the generation of GQD and pGr simultaneously. A longer oxidation time increased the quantity of GQDs and also resulted in a higher photoluminescent (PL) quantum yield. The PL quantum yield of GQD formed after 72 h of the oxidative treatment (GQD-72) was 15.8%, which is greater than the previous reported values. The TEM images showed matching sizes for GQDs and the pores present in pGr, implying that the pores are generated by the removal of GQDs from graphene during the oxidative treatment. Since pore openings are expected to give higher levels of unsaturation and defect sites in the system and are thus being treated as fertile regions for heteroatom doping, pGr-72 was further subjected to nitrogen (NpGr-72). NpGr-72 displayed excellent activity towards the electrochemical oxygen reduction reaction (ORR) compared to nitrogen-doped non-porous graphene (NGr) and many other reported nitrogen-doped carbon materials. A distinct 50 mV gain in the overpotential and 2.5 times increment in the kinetic current density (j(k)) have been achieved in the case of NpGr-72 compared to NGr. Interestingly, unlike NGr, NpGr-72 effectively reduced the oxygen molecule with a greater involvement of the preferred four-electron pathway. Additionally, the overpotential difference of NpGr-72 with respect to 20 wt% Pt/C is only 60 mV. Additionally, in a single cell evaluation under anion exchange membrane fuel cell (AEMFC) conditions, NpGr-72 exhibited a maximum power density of 27 mW cm(-2), which is significantly higher than the corresponding value of 10 mW cm(-2) obtained for NGr. Thus, the overall enhancement in the performance characteristics of NpGr-72 is attributed to the higher content of nitrogen (7.8 wt%) and its large proportion of desired chemical environment, which could be established by utilizing the high level of carbon unsaturation around the pore openings.